Topology-Aware Navigation in Large Networks - Moscovich, Tomer; Chevalier, Fanny; Henry Riche, Nathalie; Pietriga, Emmanuel; Fekete, Jean-Daniel (In CHI'09: Proceedings of the twenty-seventh annual SIGCHI conference on Human factors in computing systems, 2009)
Applications supporting navigation in large networks are used every days by millions of people. They include road map navigators, ight route visualization systems, and network visualization systems using node-link diagrams. These applications currently provide generic interaction methods for navigation: pan-and-zoom and sometimes bird’s eye views. This article explores the idea of exploiting the connection information provided by the network to help navigate these large spaces. We visually augment two traditional navigation methods, and develop two special-purpose techniques. The first new technique, called “Link Sliding”, provides guided panning when continuously dragging along a visible link. The second technique, called “Bring & Go”, brings adjacent nodes nearby when pointing to a node. We compare the performance of these techniques in both an adjacency exploration task and a node revisiting task. This comparison illustrates the various advantages of content-aware network navigation techniques. A significant speed advantage is found for the Bring & Go technique over other methods.